070. Total Bowel Obstruction and Secondary Renal Impairment Following Bajakah Root Ingestion: Case Report - Irnawati, Farida Dwi; Sulistyo, Heru (JBN (Jurnal Bedah Nasional), 2024)
Background : Total bowel obstruction is a critical condition often caused by malignancies and adhesions or rare caused by foreign bodies. The bajakah root is a herbal medicine in Dayak community (Central Kalimantan), traditionally used to treat any diseases. This report presents a unique case of bowel obstruction due to bajakah root, and renal impairment as a complication. Case :  A 62 years old female without any psychiatric disorders with history bajakah root consumtion complaint difficult defecation and green vomiting. Physical examination showed abdominal distention with collapsed rectal ampulla. Laboratory results revealed renal impairment. Imaging studies confirmed total bowel obstruction. Exploratory laparotomy identified ileoileal and ileo-omental adhesions with 0.5x0,5 cm ileum perforation 120 cm distal to the ligament of Treitz and a 2x2 cm wooden foreign body 10 cm distal from the perforation site. Surgical management included adhesiolysis, wedge excision of the ileum, foreign body extraction and anastomosis. Conclusion: Total bowel obstruction, renal impairment, bajakah, foreign body, foreign body extraction.